2009
DOI: 10.1186/1475-2875-8-301
|View full text |Cite
|
Sign up to set email alerts
|

Treatment-seeking for febrile illness in north-east India: an epidemiological study in the malaria endemic zone

Abstract: BackgroundThis paper studies the determinants of utilization of health care services, especially for treatment of febrile illness in the malaria endemic area of north-east India.MethodsAn area served by two districts of Upper Assam representing people living in malaria endemic area was selected for household survey. A sample of 1,989 households, in which at least one member of household suffered from febrile illness during last three months and received treatment from health service providers, were selected ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
62
1
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 79 publications
(67 citation statements)
references
References 20 publications
3
62
1
1
Order By: Relevance
“…Selling paracetamol alone is prohibited because, while attenuating the fever, it delays the administration of appropriate antimalarial treatments e which can increase lethality (Chaturvedi et al, 2009;McCombie, 1996).…”
Section: Sense Of Credibility and Legitimacy In Being Part Of Local Pmentioning
confidence: 99%
“…Selling paracetamol alone is prohibited because, while attenuating the fever, it delays the administration of appropriate antimalarial treatments e which can increase lethality (Chaturvedi et al, 2009;McCombie, 1996).…”
Section: Sense Of Credibility and Legitimacy In Being Part Of Local Pmentioning
confidence: 99%
“…Easy availability, less fees and better responsiveness were probably in favor of visiting nonqualified practitioners. [13][14][15] Multiple studies from Nepal reported that 26% of people visited traditional healers exclusively while only 19% first visited formal health care institutions, medical shops without consultation were common source of medicines, and around half of episodes of childhood illnesses were treated by pharmacists. [16][17][18] In a study by Gera et al, from on women of Uttarakhand all respondents went for traditional/home remedies/other remedy initially and only 6.5% opted allopathic medicine as the first choice.…”
Section: Health Care Seeking Behaviormentioning
confidence: 99%
“…In limited resource settings fever may be treated empirically or self treated due to lack of access to diagnostic tests. Thus knowledge of local prevalence of infections is critical in order to target clinical work up and treatment as shown in Mittal et al, (2015) and Chaturvedi et al, (2009). Studies from Tamilnadu by Anugrah Chrispal et al, (2010), Rani et al, (2016), Gopalakrishnan et al, (2013) and Kerala by Andrews et al, (2014) showed most of the AUFI are treatable and reduction in mortality if they were diagnosed earlier.…”
Section: Issn: 2319-7706 Volume 6 Number 5 (2017) Pp 954-962mentioning
confidence: 99%